ISLAMIC HIGHER EDUCATION IN POST-CONFLICT ACEH: Generation Z Students, Religious Knowledge and Professional Interests - Barus, Jumat; Husaini, Husaini; Ja'far, Ja'far; Noor, Umar Muhammad (State Islamic University North Sumatra, 2024)
Abstract: This study examines the recent development of Islamic universities in post-conflict Aceh. Government data shows that Indonesia will face a demographic bonus era in the future, where the productive age population will be greater than the non-productive age population. As much as 27.94% of Indonesia's population is Generation Z, born between 1997 and 2012. With a pragmatic and realistic character, those aged 12-27 are currently studying at the secondary to tertiary level. In this context, this study examines the professional interests of the Generation Z group in contemporary Aceh. As qualitative research, this study has shown that some Generation Z groups continue to choose Islamic universities as their first choice of university. In public Islamic universities, the main trend of their professional interests is education and economics, with less interest in other fields such as sharia, and ushuluddin and da'wah. Ease of employment has been their most important reason for choosing the disciplines of education and economics. In other cases, a group of Generation Z has kept Islamic disciplines as their professional interest, and their goal in this field is to become religious scholars or teachers. Although considered a pragmatic and realistic generation, many of them still prioritize an idealistic attitude in their academic career.Keywords: generation Z student, Islamic higher education, religious knowledge, professional interests